2010
DOI: 10.1590/s1413-35552010000600009
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do índice de respiração rápida e superficial (IRRS) calculado de forma direta e indireta no pós-operatório de cirurgia cardíaca

Abstract: Objectives:To compare and to analyze whether the values of rapid shallow breathing index (RSBI) determined by a ventilator display and a digital ventilometer were correlated. Methods: Twenty-two adult patients (17 males and 5 females) in the postoperative period of cardiac surgery and in mechanical ventilation were studied. Prior to the data collection, each patient was evaluated, received physical therapy, in order to promote bronchial hygiene and pulmonary reexpansion, and was positioned in elevated dorsal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…We obtained the RSBI values from the ventilator display. It has been proven that RSBI calculated from values obtained by direct ventilometry and the one obtained through the display of the mechanical ventilator are highly correlated [ 26 ]. RSBI rate was calculated by using the following formula: (RSBI 2–RSBI 1)/RSBI 1 × 100, where RSBI 1 is the initial RSBI value (fifth minute) and RSBI 2 is the second value measured at the end of 120 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the RSBI values from the ventilator display. It has been proven that RSBI calculated from values obtained by direct ventilometry and the one obtained through the display of the mechanical ventilator are highly correlated [ 26 ]. RSBI rate was calculated by using the following formula: (RSBI 2–RSBI 1)/RSBI 1 × 100, where RSBI 1 is the initial RSBI value (fifth minute) and RSBI 2 is the second value measured at the end of 120 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Inicialmente foram coletadas informações relacionadas ao sexo, idade, cor, IMC, tipo de cirurgia, intercorrências intraoperatórias, utilização de circulação extracorpórea e tempo de anoxia dos participantes da pesquisa, através do prontuário. Os participantes da pesquisa foram avaliados no período de pós-operatório de cirurgia cardíaca durante o processo de Ferraris -Europa/Reino Unido (Lessa et al, 2010). Para esta análise, o paciente foi posicionado em decúbito dorsal com elevação da cabeceira em 45°.…”
Section: Parâmetros Avaliadosunclassified
“…Some studies have indicated that calculating the RSBI using data from the ventilator can interfere with the value reached. 5 , 10 , 11 , 12 , 13 Obtaining it in PSV mode, even with low pressure levels, generates lower RSBI values than from spontaneous breathing with the use of the ventilometer. 5 , 11 , 13 , 14 , 15 , 16 When comparing the RSBI obtained by the ventilometer with the one from Continuous Positive Airway Pressure (CPAP) mode, the data are conflicting.…”
Section: Introductionmentioning
confidence: 99%